To look like a lawyer: anatomopolitics within the hidden curriculum in Mexican legal dducation (2021)
In Volume 1 of The History of Sexuality, Foucault defines two branches of biopolitics: one centered on controlling and regulating populations, the other, seemingly developed earlier, "centered on the body as a machine: its disciplining, the optimization of its capabilities, the extortion of its forces, the parallel increase of its usefulness and its docility, its integration into systems of efficient and economic controls, all this was ensured by the procedures of power that characterized the disciplines: an anatomopolitics of the human body" (Foucault, 1998, p. 139). We propose that the hidden curricula within Mexican legal education contains strong anatomopolitical components which regulate the bodies and appearances of law students under the discourse of "formality" and "professional image". Following the approaches made by Entwistle (2001), we extend anatomopolitics not only to the body, but it's public presentation, i.e. its dressing. "Foucault's notion of discourse can enable the analysis of fashion as a discursive domain which sets significant parameters around the body and its presentation" (Entwistle, 2001, p. 39). In order to present this theory, we interviewed 40 law students from 22 different law schools in Mexico, and 15 teachers from 7 law schools about their lived experience.